Implementasi Program â€œWe Love Baliâ€ Berbasis CHSE (Clean, Health, Safety, Environment) dalam Pemulihan Pariwisata Bali - I Made Wimas Candranegara; I Wayan Mirta; Kadek Agus Febriana Putra (Journal of Contemporary Public Administration, 2021)
We Love Bali is a program created by the Ministry of Tourism and Creative Economy aiming to help tourism businesses in Bali to grow in the midst of new normal era while still paying attention to health protocols. This activity is supported by programs that can make tourists interested with the situation of tourist destinations in Bali. It is hoped that this program will be able to make tourism in Bali recover and the economy will rebound and people are able to return to their normal activities in the midst of the Covid 19 pandemic. This paper employs literature studies and interview to examine the implementation of the program. The descriptive result that emphasizes interviews with tourism actors are supported by data from tourists visiting Bali. The results of this study indicate that We Love Bali program is able to restore the economic condition of the Balinese people to a better condition. And also We Love Bali program is one of the programs implemented to help tourism businesses and the creative economy including hotels, travel businesses, transport businesses, tour guides, restaurants, tourist destinations, MSMEs, and others.